Ki-67 expression in mature B-cell neoplasms: a flow cytometry study - Marcondes,Natália (2018)
SUMMARY OBJECTIVE: Ki-67 is a nuclear protein associated with cellular proliferation in normal or leukemic conditions that can help identify more aggressive diseases and is usually evaluated with immunohistochemistry. The aim of this was to assess Ki-67 expression on mature B-cell neoplasms samples with flow cytometry immunophenotyping. METHOD: After surface staining with CD19 and CD45, intracellular staining for Ki-67 was performed in leukemic mature B-cells. Ki-67 expression was evaluated with flow cytometry. RESULTS: Ki-67 expression was higher in mantle cell lymphoma, Burkitt lymphoma, and diffuse large B-cell lymphoma cases. It was also associated with CD38 mean fluorescence intensity. CONCLUSIONS: Ki-67 expression evaluated by flow cytometry can be a useful tool in the diagnosis of mature B-cell neoplasms. More studies are needed to validate Ki-67 assessment with flow cytometry immunophenotyping.